An Introduction to corporate governance and the SEC - SKOUSEN, K Fred (Thomson, 2005)
Recent traumatic events in the financial markets, such as the fall of Enron, World Com, and Arthur Andersen, have led to an increased emphasis on corporate governance and on the regulatory bodies overseeing the capital markets and the financial professions. This emphasis is reflected in accounting and business curricula across the nation. Educational materials that appropriately highlight the importance of the SEC, as well as the new laws that apply to corporate reporting, ethics, and guidelines for corporate governance, are scarce, despite their increasingly important role. Few titles that can serve as either a supplement or as a primary text exist that focus on the SEC as the body for overseeing financial reporting and corporate responsibilities.